DESKRIPSI AKULTURASI TERHADAP PENYAJIAN MUSIK PADA UPACARA ADAT PERKAWINAN SIMALUNGUN DI DESA SARIBUDOLOK KECAMATAN SILIMAKUTA KABUPATEN SIMALUNGUN - Radot Situmorang (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The ethnic diversity of Saribudolok Village, Silimakuta District, Simalungun Regency, has created a setting for cultural interaction that influences the development of music in Simalungun traditional wedding ceremonies. This phenomenon provides the basis for examining how cultural acculturation shapes changes in musical composition, performance practices, and musical structure within traditional ceremonial contexts. The study employed a descriptive qualitative approach from an ethnomusicological perspective through field observations, in-depth interviews, documentation, and interpretative data analysis. The findings reveal that the ceremonial sequence continues to preserve the fundamental structure of Simalungun tradition, while changes occur in the musical elements performed during the ceremony. The replacement of the traditional gondang ensemble with the keyboard has been accompanied by a shift in the function of music from ritual accompaniment to entertainment, the increasing use of Toba and Karo repertoires in ceremonial performances, and the declining transmission of traditional songs to younger generations. Furthermore, the analysis of the song Sibirong-Birong demonstrates the integration of Batak pentatonic melodic idioms with the Western diatonic scale, reflecting a process of musical adaptation without eliminating local musical characteristics. These findings indicate that changes in musical composition result from cultural negotiation, enabling the community to preserve the musical identity of Simalungun while adapting to the social dynamics of a multiethnic society. This study enriches the field of ethnomusicology by advancing the understanding of musical acculturation and providing a foundation for strengthening the documentation, preservation, and regeneration of Simalungun traditional music. ABSTRAK Keberagaman etnis di Desa Saribudolok, Kecamatan Silimakuta, Kabupaten Simalungun, menciptakan ruang interaksi budaya yang berpengaruh terhadap perkembangan musik dalam upacara adat perkawinan Simalungun. Penelitian ini bertujuan mendeskripsikan proses pelaksanaan upacara adat perkawinan, mengidentifikasi bentuk akulturasi yang memengaruhi komposisi musik, serta menganalisis penyajian dan struktur musikal yang berkembang sebagai dampak interaksi antaretnis. Penelitian menggunakan pendekatan deskriptif kualitatif melalui observasi lapangan, wawancara mendalam, dokumentasi, dan analisis data secara interpretatif terhadap temuan etnomusikologis. Hasil penelitian menunjukkan bahwa rangkaian upacara adat masih mempertahankan struktur pokok tradisi, meskipun beberapa unsur telah mengalami penyesuaian akibat interaksi budaya Batak Simalungun, Batak Toba, dan Batak Karo. Akulturasi tercermin pada perubahan instrumen dari ansambel gondang menuju keyboard, pergeseran fungsi musik dari media ritual menjadi sarana hiburan, dominasi repertoar Toba dan Karo dalam prosesi adat, serta berkurangnya pewarisan lagu-lagu tradisional kepada generasi muda. Analisis terhadap lagu Sibirong-Birong memperlihatkan perpaduan idiom melodi pentatonis Batak dengan sistem tangga nada diatonis Barat sebagai bentuk adaptasi musikal. Temuan ini menegaskan bahwa perubahan komposisi musik merupakan konsekuensi dari perubahan cara pandang masyarakat terhadap fungsi musik dalam adat, sekaligus memberikan kontribusi bagi penguatan kajian etnomusikologi dan menjadi dasar bagi upaya pelestarian serta regenerasi musik tradisional Simalungun.